DETERMINASI PENANAMAN MODAL ASING ASEAN-5 TAHUN 2001-2013 - Dianti Tri Ighni; Ellyana Amran (Media Ekonomi, 2015)
Foreign direct investment (FDI) has been the important ASEAN's growth economic source, bring the capital investment, technology, and management's knowledge which conduct for economic growth. The purpose of this research is to know the dominant factor which determine the magnitude of the foreign investment in ASEAN-5 2001-2103 period. The country which reseaerched is five of ASEAN country that are, Indonesia, Vietnam, Singapore, Thailand and Malaysia. From this research, the most determining factor of FDI value in a significant manner for a whole ASEAN, so it can give suggestion policy which appropriate to pull FDI. By using panel data analysis and software STATA 12 it help seen that  the factor which influence of FDI in  ASEAN-5 are Growth of  GDP, inflation, and trade openness. The Research which use annual data from Worldbank, Bank of Indonesia and IMF. The result of the research conclude that independent variable of Growth of  GDP and Trade Openness all of that is significant for explain FDI since p-score from t-statistics which less from five percent and thus have FDI influence in ASEAN-5.